Converting Mall-Apartments and Hotels Into Covid-19 Emergency Hospitals - Hanna Wijaya,; St. Laksanto Utomo, (Jurnal Indonesia Sosial Sains, 2021)
The outbreak of the Coronavirus Disease 19 (COVID-19) which afterwards became a pandemic, impacted the world. Because of the rapid spread and ongoing research, World Health Organization (WHO) and the government had created regulations that are constantly changing. President Joko Widodo recommended to utilize the unused buildings as emergency hospitals in order to accelerate the handling of the Covid-19 virus in Indonesia. Lippo Group's owner wants to assist the government by converting Plaza Mampang Mall into Siloam Hospital (a Covid-19 emergency hospital), which will be housed in the same building as the Nine Residence Apartments. As a result, the inhabitants of the unit protested regarding the building changing function. The research focuses on the function of apartement to a COVID-19 emergency hospital, as well as the obligations of building owners for the transfer of functions. For COVID-19, not only Nine Residence mall-apartment but also some hotels served as emergency hospitals. This study employs normative juridical research, with the law approach and the case approach as approaches. Secondary data was used as a source of information, and the research material was obtained through a library study. The findings of this study show that the building owner's procedure of transferring function to the mall-apartment must meet administrative and technical requirements in accordance with the building's purpose. If the function transfer of apartement nine residence, had a bad results to the owner of the apartment unit, then the owner of the building must be responsible to the owner of the apartement unit.